Implementation of the Argument-Driven Inquiry (ADI) Model in Physics Learning of 2012-2021: Bibliometric Analysis - Setyo Admoko; Kafa Pramitha Anggraini Indhira Artanti; Eko Hariyono; Madlazim Madlazim (Indonesia Emerging Literacy Education, 2022)
Argumentation is a core practice of scientific discourse. One of the problems in learning science is the low level of argumentation skills of students. Efforts to improve argumentation skills include implementing the Argument-Driven Inquiry (ADI) learning model. This study aims to identify the contribution and find out the trend of applying ADI in physics learning in 2012-2021. The method used in this research is a bibliometric analysis based on Scopus data with the help of MS Excel and VOSviewer to visualize the metadata obtained. The results of this study obtained 100 documents. The development of ADI every year does not have a significant increase in the number of publications produced. Research visualization using VOSviewer produces 14 clusters and is closely related to argumentative learning, guided inquiry, and so on. Based on the results of this study, it can be concluded that the ADI has several contributions to science learning, mostly done in Chemistry, and it is still rare in Physics, so it can be an opportunity for further research. It is hoped that further research can discuss more deeply the ADI learning model, which is applied to physics learning to improve students' argumentation skills.